Optimizing Teacher Job Satisfaction Among Special Education Teachers Through Emotional Intelligence With Social Support As A Moderator - Dinda Khairunnisa; Riva Nadia Putri; Nur Hasmawalati (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
This study aims to analyze the influence of emotional intelligence and social support on the job satisfaction of teachers in Special Schools (SLB). The analysis was conducted through three stages of construct validity testing and regression analysis. The results indicate an improvement in indicator validity across the stages, although some indicators remained weak and required elimination. Regression analysis showed that emotional intelligence had a strong and significant positive effect on teacher job satisfaction, with a path coefficient of 0.567 and a significance value of 0.000 (p < 0.05). Meanwhile, social support initially showed no significant effect but was later found to be significant in the final hypothesis testing, with a significance value of 0.026 (p < 0.05). The coefficient of determination (R² = 0.408) indicates that both independent variables jointly explained 40.8% of the variance in job satisfaction, while the remaining variance was influenced by other factors outside the research model. These findings highlight the importance of internal factors, such as emotional intelligence, and external factors, such as social support, in enhancing teacher job satisfaction in special education. The study further emphasizes the balance between personal capabilities and environmental support in shaping positive work attitudes and opens opportunities for future research.